PENGEMBANGAN SMART INFRASTRUCTURE PADA ASPEK PRASARANA PERKOTAAN DI KOTA BANDARLAMPUNG - Diah Mayang Sari; Muhammad Zainal Ibad; Adinda Sekar Tanjung (Lembaga Penelitian, Pengabdian Masyarakat, dan Penjaminan Mutu (LP3) ITERA, 2022)
The city of Bandar Lampung, which is the capital of Lampung Province, which is currently not included in the 100 smart city movement in Indonesia, has tried to keep up with and make Bandar Lampung a smart city. Marked by the vision of the City of Bandar Lampung, namely